Reassessing the Principle of Utility in the Revocation of Bankruptcy Adjudications: Implications for Legal Practice - Ivida Dewi Amrih Suci; R. Murjiyato; Mohd Zamre Mohd Zahir; Sudiyana Sudiyana (Journal of Private and Commercial Law, 2024)
This paper reassesses the principle of utility in the revocation of bankruptcy adjudications while addressing a critical gap in bankruptcy law concerning undivided marital assets following divorce. Article 64(1) of the Indonesian Bankruptcy Law establishes that bankruptcy involving spouses under a unity of assets is treated as a single estate. However, the law remains silent on situations where spouses have divorced but their shared assets remain undivided, and one or both parties are subsequently declared bankrupt in separate proceedings. In practice, such cases are handled by different commercial courts, reinforcing their status as distinct legal subjects and raising the question of whether consolidation of bankrupt estates is permissible or desirable. Using a normative legal methodology, this study draws on Kees Schuit’s legal system theory and the goal-oriented theory of law, grounded in Gustav Radbruch’s triad of certainty, utility, and justice. It critically examines how the principle of utility is applied in determining whether revocation or consolidation of bankruptcy adjudications serves a meaningful legal purpose. The analysis reveals inconsistencies in judicial reasoning, particularly where utility is narrowly interpreted as economic benefit, neglecting considerations of fairness, procedural coherence, and legal certainty. The paper’s main contribution lies in proposing a structured framework for interpreting utility that integrates both doctrinal clarity and practical guidance. It also advances the argument that undivided post-divorce assets may, under certain conditions, justify consolidation based on principles of integrity and efficiency. This approach enhances predictability in legal practice while preserving judicial flexibility. Ultimately, the study contributes a prescriptive perspective to bankruptcy law by bridging doctrinal gaps